Electronic Cigarette Cessation in Youth and Young Adults: A Case Series. (June 2021) - Sikka, Gautam; Oluyinka, MopeninuJesu; Schreiber, Raiza; Galiatsatos, Panagis
Introduction: Electronic cigarette (e-cigarette) usage use has increased exponentially, especially in youth and young adults. For many, the usage of these products results in a severe addiction, one that is difficult to discontinue. Further, e-cigarette cessation is challenging as there are no specific guidelines directing such medical management for patients and their respective clinicians. Here, we report a case series of patients who we are attempting to wean from e-cigarettes with medical guidance. Methods: Six patients who self-reported daily e-cigarette usage and were enrolled in our Tobacco Treatment Clinic (TTC) were followed for 12-months. An inventory of the e-cigarette product and usage was captured, along with responses to identify when the patients experienced majority of their cravings. Co-morbidities, if present, were documented. Documentation of interventions, counseling with or without pharmacological therapies, were captured. Primary outcome was cessation at 6-months. Results: The 6 patients enrolled in clinic ranged in age from 17 to 31 years, with 4 of the patients identifying as males and 2 as females. Patients were using e-cigarettes for 1 to 6 years prior to enrolling into the TTC. As for interventions, all patients received counseling and pharmacological interventions in the form of nicotine replacement therapies (NRTs). Three of the 6 patients were weaned off e-cigarettes by 6-months, with a fourth patient weaned off at the 8-month mark. Variables identified as barriers to cessation included non-compliance with medical regimen and peer influence. Discussion: Here we present a case series of attempting to wean persons from electronic cigarettes use. Given the lack of international guidelines in e-cigarette addiction management, we believe this case series will be of value for clinicians and their patients. Further studies are warranted to help patients with e-cigarette addiction in their attempt at cessation.